Perceived Effects of Computer-Based Examination (CBE) on Essay Writing Skills of Undergraduates in Ambrose Alli University, Ekpoma, Edo State - Olusi F. I; Onobun Angela; Anolu Easter (RIRAI Publisher, 2021)
The study examined the perceived effects of Computer-Based Examination (CBE) on essay writing skills of undergraduates in Ambrose Alli University, Ekpoma, Edo State. One research question was raised and answered while the three hypotheses were formulated and tested in the study. The descriptive research design was adopted for the study. The population of this covered all the 27,388 regular undergraduate students in Ambrose Alli University, Ekpoma. A sample size of 546 students were selected for the study. The proportional random sampling technique was used to select 2% of the total number of students across each of the faculties in the institution. The instrument used for the collection of data was developed by the researcher and titled: “Computer Based Examination Perception Questionnaire (CBEPQ)”. The instrument has a reliability alpha (α) of 0.78. The research question was analysed using the mean ( ) and standard deviation (S.D) while the t-test statistics for two independent samples was used to test hypothesis 1, 2 and 3 at 0.05 level of significance. Based on findings, it can be concluded that computer-based examination (CBE) has effect on their essay writing skills as undergraduates in Ambrose Alli University, Ekpoma, Edo State. Hence, it is concluded that undergraduate students of Ambrose Alli University, Ekpoma perceived that computer-based examination (CBE) has effect on their essay writing skills. Female undergraduates of Alli University, Ekpoma, Edo State had higher perception on the effect of CBE on essay writing but their perception of CBE on essay writing did not differ by age and level of study.